Pelatihan Pembuatan Wrench menggunakan Teknik kerja Bangku Bagi Mahasiswa di Growth Centre LLDIKTI Wilayah - I - Hermawan, Indra; Aldori, Yopan Rahmad; Hidayat, Taufik Wal; Marwan, Marwan (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
This training aims to provide students with understanding and practical skills in making wrenches using bench work techniques. A Wrench is a tool used in various industrial and mechanical work, essential in tightening and loosening bolts and nuts. Through this training, students will be introduced to the basic principles of bench work techniques, including hand tools and an understanding of the materials used. The workshop will emphasize practical processes, from reading technical drawings to the final finishing stages. Students will receive instructor guidance in bench work and manufacturing techniques, enabling them to develop valuable hands-on skills in a manufacturing environment. By attending this training, students are expected to be able to apply the learning of the manufacturing process in actual practice. The training results show that all students can complete the products given even though there are still weaknesses, such as less accurate and precise products, because students do not have sufficient experience in hand skills and the use of simple bench work tools.